2017
DOI: 10.1515/pcssr-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Former College Student-Athletes’ Wellness

Abstract: IntroductionCollege graduation is accompanied by a challenging transition into the real world, which like many other major life transitions, may be distressing and can affect individuals' wellness (Hart & Swenty 2015). For student-athletes (SAs) who already display reduced levels of wellness (Watson & Kissinger 2007), transitioning from college may be an especially treacherous time. Research is needed to better understand the aspects of wellness that are impacted during SA's transition out of sport.One method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Coaches may help athletes reach their maximum potential while simultaneously developing a culture of resilience and wellbeing by encouraging enough sleep, highlighting the value of nutrition, and educating athletes on lifestyle issues that affect performance. Setting priorities for health and wellness fosters a positive atmosphere that inspires athletes and coaches to make healthy decisions, as noted by Warehime et al (2017). This results in happier, more engaged people on and off the court.…”
Section: Resultsmentioning
confidence: 95%
“…Coaches may help athletes reach their maximum potential while simultaneously developing a culture of resilience and wellbeing by encouraging enough sleep, highlighting the value of nutrition, and educating athletes on lifestyle issues that affect performance. Setting priorities for health and wellness fosters a positive atmosphere that inspires athletes and coaches to make healthy decisions, as noted by Warehime et al (2017). This results in happier, more engaged people on and off the court.…”
Section: Resultsmentioning
confidence: 95%
“…Collegiate athletes that maintain realistic expectations surrounding their athletic careers (such as the DIII participants in this study) coupled with career maturity (using campus career and academic resources along with proactive planning) report a more positive transition to life after sports (Navarro, 2014;Warehime et al, 2017). Navarro (2014) found when collegiate athletes choose their major based on their academic skillset, familial influence, and person-JADE Bowling Green State University -https://scholarworks.bgsu.edu/jade/ al passions they were more active in the preparation process for their chosen career field.…”
Section: Moving Out: Redefining Oneselfmentioning
confidence: 98%
“…Athletic retirement experiences are diverse, in part because there are so many potential variables that can play a role in one's decision, or requirement, to retire. Researchers have reported both successful (Martin, Fogarty, & Albion, 2014;Sinclair & Orlick, 1993;Stokowski, Paule-Koba, & Kaunert, 2019;Warehime, Dinkel, Bjornsen-Ramig, & Blount, 2017) and unsuccessful (Jewett, Kerr, & Tamminen, 2018) athlete retirement transitions. For example, Martin and colleagues' (2014) study uncovered that athletes who retired on their own accord reported an increase in life satisfaction, suggesting that these individuals experienced a positive sport retirement.…”
Section: Successful Athlete Retirement Transitionsmentioning
confidence: 99%